Mutation-specific pathophysiological mechanisms define different neurodevelopmental disorders associated with SATB1 dysfunction - Hoed, Joery den; de Boer, Elke; Voisin, Norine; Dingemans, Alexander J. M.; Guex, Nicolas; Wiel, Laurens; Nellaker, Christoffer; Amudhavalli, Shivarajan M.; Banka, Siddharth; Bena, Frederique S.; Ben-Zeev, Bruria; Bonagura, Vincent R.; et al. (The American journal of human genetics, 2021)
Whereas large-scale statistical analyses can robustly identify disease-gene relationships, they do not accurately capture genotype-phenotype correlations or disease mechanisms. We use multiple lines of independent evidence to show that different variant types in a single gene, SATB1, cause clinically overlapping but distinct neurodevelopmental disorders. Clinical evaluation of 42 individuals carrying SATB1 variants identified overt genotype-phenotype relationships, associated with different pathophysiological mechanisms, established by functional assays. Missense variants in the CUT1 and CUT2 DNA-binding domains result in stronger chromatin binding, increased transcriptional repression, and a severe phenotype. In contrast, variants predicted to result in haploinsufficiency are associated with a milder clinical presentation. A similarly mild phenotype is observed for individuals with premature protein truncating variants that escape nonsense-mediated decay, which are transcriptionally active but mislocalized in the cell. Our results suggest that in-depth mutation-specific genotype-phenotype studies are essential to capture full disease complexity and to explain phenotypic variability.